Laboratory and numerical simulations of light nonaqueous phase liquid (LNAPL) in unsaturated zone - Kamaruddin, Samira Albati; Sulaiman, Wan Nor Azmin; Zakaria, Mohamad Pauzi; Abd Rahman, Norhan (2009)
The contamination of hydrocarbons in soil and groundwater by fuels and industrial chemicals has become a problem of growing concern. The contaminated groundwater is not only unsafe for human and animal consumption but also not suitable for irrigation purposes. The leaking from underground storage tanks (USTs) and pipelines, hazardous waste sites and surface spills are the general sources of nonaqueous phase liquids (NAPLs). The NAPLs is a common term used in hydrogeology to describe the immiscible, separate liquids phase when in contact with water and/or air that occurred in subsurface environment. These liquids typically have different density and viscosity than water (Charbeneau, 2000). A NAPL with a density less than water is classified as light nonaqueous phase liquid (LNAPL), and a NAPL denser than water is classified as dense nonaqueous phase liquid (DNAPL).